(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
We live in a world in constant evolution. The information technology and communication have advanced to the point of change the everyday life of society, which performed more and more shares via the Internet. Due to globalization in recent years NET, SMEs have been changing the mode of marketing their goods or services. They are more and more which are incorporated into this new form of business, which directly impacts on the country’s economy. The cause is due to that, both companies and consumers, enjoy certain benefits resulting from e-commerce, which will be analysed in the present work. This work dealt with research on the impact that e-Commerce generated in SMEs in the city of Santa Rosa, emphasizing the impact on consumers. To do this, work began referring to the international context, analyzing then generally at level country, to then address the issue especially in the pampean capital. You were also asked about their advantages and disadvantages doing a SWOT analysis. Finally, investigated the number of taxpayers using e-commerce doing surveys, whereas a sample of ten SMEs.